Analisis keterlibatan orang tua dalam mengembangkan kemampuan literasi siswa berkebutuhan khusus di SLB-C Negeri Tulungagung - dewi ayu nurha sonia sonia (UIN Mataram, 2024)
ABSTRACT Literacy is a reading and writing skill that is very important in the learning process. It is the initial ability that every student must have which will affect achievement and the subsequent learning process. However, the reality is that not many children with special needs are able to literate well. With this, the need for support and assistance both at school and at home, as well as providing media that can help and increase students' attractiveness in literacy / learning, because of their physical and motor conditions which are one of the obstacles in every literacy / learning process.The purpose of this study is to determine the involvement of parents in developing the literacy skills of students with special needs in SLB-C Negeri Tulungagung district. This research uses a qualitative approach and type of case study research by conducting research at SLB-C Negeri Tulungagung. The research subjects consisted of 8 informants, 6 informants from guardians of elementary school students and 2 informants from elementary school teachers at SLB-C Negeri Tulungagung. Data collection was obtained from observation, documentation, and interviews. Analysis with data reduction, data presentation, and conclusions. From the research that has been done, the research findings reveal three findings, namely: (1).Parents of students with special needs are very involved in every student's literacy / learning activities both at home and at school. (2).Students are able to interact with fellow friends in the neighborhood. (3) During school learning, students are able to literate and learn with the assistance and direction of the teacher. Keywords: Parental Involvement, Literacy, Students with Special Needs.